قلق المستقبل المهني وعلاقته بالتوافق الأكاديمي لدى الطلبة المقبلين على التخرج - حمامة, عمار; خليل, امنة (جامعة الوادي - University of Eloued, 2023)
ملخص : هدفت هذه الدراسة للكشف عن العلاقة بين قلق المستقبل المهني والتوافق الأكاديمي لدى الطلبة المقبلين على التخرج. وقد أجريت الدراسة اعتمادا على المنهج الوصفي الإرتباطي ، حيث تم استخدام مقياس قلق المستقبل المهني من إعداد" مشري، فلاح ، جوادي"(2018) ومقياس التوافق الأكاديمي من إعداد "عديلي"(2016) وطبقت الأداتان على عينة قوامها 150 طالب وطالبة بطريقة عرضية ، من طلبة ليسانس بجامعة الشهيد حمه لخضر بالوادي من التخصصات التالية: علوم اقتصادية ، إرشاد وتوجيه ، بيوكيمياء. وتوصلت الدراسة في الأخير إلى عدم وجود علاقة ارتباطيه بين قلق المستقبل المهني والتوافق الأكاديمي لدى الطلبة المقبلين على التخرج. - لا توجد فروق ذات دلالة إحصائية في مستوى قلق المستقبل المهني لدى الطلبة المقبلين على التخرج باختلاف الجنس. - لا توجد فروق ذات دلالة إحصائية في مستوى التوافق الأكاديمي لدى الطلبة المقبلين على التخرج باختلاف الجنس. - توجد فروق ذات دلالة إحصائية في مستوى قلق المستقبل المهني لدى الطلبة المقبلين على التخرج باختلاف التخصص. - توجد فروق ذات دلالة إحصائية في مستوى التوافق الأكاديمي لدى الطلبة المقبلين على التخرج باختلاف التخصص. Abstract : This study was aimed at revealing the relationship between the concern of the professional future and the academic compatibility of students coming to graduate The study was conducted on the basis of the descriptive correlation method where the measure of future anxiety was used by the preparation of Mashri, Falah, Jawadi (2018) and the academic compatibility scale of Adly's preparation (2016) and applied the instruments to a sample of 150students and students in an incidental manner from the students of The University of Hama for the Greens of the Valley from theThe study concluded in the end that there is no correlation between the concern of the career and the academic compatibility of students coming to graduate. - There are no statistically significant differences in the level of career anxiety among students who are coming to graduate by gender. - There are no statistically significant differences in the level of academic compatibility concern among students who are coming to graduate by gender. - There are statistically significant differences in the level of concern for the career of students who are coming to graduate in different disciplines. - There are statistically significant differences in the level of concern of academic compatibility among students coming to graduate according to specialization. following disciplines economics, guidance and orientation, biochemistry.
مقال
Keywords: قلق المستقبل المهني ; التوافق الأكاديمي ; الطلبة المقبلين على التخرج; professional future anxiety; academic compatibility; Students who are about to graduate